Development of linguoculturological competence using visual aids when teaching Russian as a foreign language - Ekaterina A. Gorlova; Olga V. Ershova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2018)
This paper presents the main types of visual aids, the inclusion of which in the process of teaching Russian as a Foreign Language is necessary. The concept of is characterized, which should be formed during the lessons in Russian as a Foreign Language, among other educational goals. The authors briefly describe the classification of the main types of visual aids, formed on the basis of the activity type of the student (language and non-language means). The paper justifies the importance of introducing various visual aids into the educational process for its intensification and increase of efficiency. There is a description of the possibilities of various visual aids for the formation of linguoculturological competence of students, which includes not only mastering the skills of using the Russian Language in various communicative situations, but also knowledge of culture, history and literature of the Russian Federation.